Case Report on Worldwide Deaths Cases of Covid 19 from December to Mid- May 2020 and Its Impact: Life Sciences-Biotechnology for prospective medical science - Sumayya Rehaman (International Journal of Life Science and Pharma Research, 2022)
The epidemic spate time has made to freeze the entire world of pandemic outbreak (Covid -19) Coronavirus disease 2019 which needs a crisis alert. WHO declared the Covid–19 of novel coronavirus as a public emergency and a pandemic outbreak? WHO report says, that in the end of mid-May, 2020 about 4,526,850 cases, 303,405 deaths (15%), 1,704,268 recovered (85%) were reported and about 81,997 total cases and 2,649 deaths have been reported in India. Moreover, the result of the outbreak has locked down many countries including China, USA, Italy, Spain, France, Germany, Japan and Vietnam. Within 23 weeks of its spread, it has affected almost 215 countries across the world. India is in the 12th most affected economy due to Global and domestic recession. The positive impact of the lockdown is on the healing of the environment pollution proved by its Air Quality index (AQI). On analysis of total affected cases and the total deaths from January to mid-May, 2020 and on comparison about 1.4% death cases are increased. The Crude Death Rate in the month of January- mid May, 2020 was 21.6, 35.1, 51.06, 70.8 and 67.02 per 1000 individuals of given time period. WHO has recommended the drugs on physician advice such as the hydroxychloroquine with the antibiotic azithromycin and antiviral drugs were acyclovir, ribavirin, ganciclovir and methylprednisolone for the Covid -19 for clinical practice. This review has briefed about coronavirus structure with virulence infection and case report on crude death rate and its impact on world economy as well as the environment.